Efektivitas Badan Usaha Milik Desa dalam Bingkai Siyasah Dusturiyah: Studi di Desa Andinete Kec. Kolono - Rahma Nur Aulia (QAIMUDDIN: Journal of Constitutional Law Review, 2025)
This study aims to analyze the effectiveness of the management of the Village-Owned Enterprise (BUMDes) Alam Sejahtera in Andinete Village, Kolono Subdistrict, from the perspective of siyasah dusturiyyah (Islamic governance). This research is a normative empirical study with a descriptive-analytical approach, examining the empirical relationship between the application of siyasah dusturiyyah principles and the effectiveness of BUMDes management. The data sources comprise both primary data, collected through observation, interviews, and documentation, as well as secondary data. Data were analyzed using techniques of data reduction, data presentation, and conclusion. The findings indicate that the management of BUMDes Alam Sejahtera has not been effective from a siyasah dusturiyyah perspective. The implementation of the five basic principles of siyasah dusturiyyah, consultation (musyawarah), justice, transparency, public welfare (kemaslahatan umum), and trust (amanah), has not been fully effective. Consultation is weak because the community has not been fully engaged in the decision-making process. Justice is uneven, as economic benefits are only enjoyed by certain groups. Transparency is low because reports and information are not openly communicated. Public welfare has not been prioritized, as existing programs fail to address the needs of the majority of residents adequately. The principle of trust is also not reflected, as accountability reports are not openly available to the public. This study recommends strengthening more inclusive consultations, equitable distribution of economic benefits, improving transparency through open reporting, designing programs based on the actual needs of the community, and enforcing the principle of trust by providing regular and accessible accountability reports.